Life Lessons in Polish Schools: Teachers’ Attitudes Towards Girls and Boys - Aleksandra Gajda (Nauki o Wychowaniu, 2022)
The aim of the study was to analyse teachers’ interactions with students in order to track the differences in the messages given to pupils depending on their gender, and to study the opinions of students about the behaviour of their teachers. As part of the research, 34 hours of lessons (divided into 17 hours of mathematics and 17 hours of Polish language lessons) were observed. Additionally, the opinions of 68 students (34 girls and 34 boys) were analysed. The study employs mixed methods of data analysis (Stromquist 2007), combining a qualitative approach based on elements of grounded theory (Glaser, Strauss 2017) with quantitative comparisons of the frequency of the teacher’s behavior, using χ2 tests. The results indicate the differing nature of teachers’ interactions with girls and boys; the number of interactions and their quality are more favourable in the case of boys. Girls are more often overlooked, and their achievements and contributions are less frequently noticed. In addition, students are aware of the differences in how they are treated by their teachers, pointing out, inter alia, to the importance of providing equal treatment to all students.